2017
DOI: 10.1136/bmjopen-2017-016395
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer mortality and associated factors in São Paulo State, Brazil: an ecological analysis

Abstract: ObjectiveIdentify the factors associated with the age-standardised breast cancer mortality rate in the municipalities of State of São Paulo (SSP), Brazil, in the period from 2006 to 2012.DesignEcological study of the breast cancer mortality rate standardised by age, as the dependent variable, having each of the 645 municipalities in the SSP as the unit of analysis.SettingsThe female resident population aged 15 years or older, by age group and municipality, in 2009 (mid-term), obtained from public dataset (Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
10

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 44 publications
0
10
0
10
Order By: Relevance
“…Therefore, evaluating the relationship between the cancer mortality and the participation rate of cancer screening is very important. Although several investigators have reported a correlation between the participation rate of other cancer screening and the respective cancer mortality (Cramer, 1974;Lazcano-Ponce et al, 2008;Harding et al, 2015, Diniz et al, 2017Lynge et al, 2017;Yoshida et al, 2018), no reports have explored the relationship between the participation rate of lung cancer screening and the lung cancer mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, evaluating the relationship between the cancer mortality and the participation rate of cancer screening is very important. Although several investigators have reported a correlation between the participation rate of other cancer screening and the respective cancer mortality (Cramer, 1974;Lazcano-Ponce et al, 2008;Harding et al, 2015, Diniz et al, 2017Lynge et al, 2017;Yoshida et al, 2018), no reports have explored the relationship between the participation rate of lung cancer screening and the lung cancer mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Low rates of mammogram screening have also been found in other low- and middle-income countries around the world, for example, in Tanzania ( Ng’ida et al., 2019 ) and Turkey ( Yılmazel, 2018 ) as well as in the rural Appalachian area of the United States ( VanDyke & Shell, 2017 ). Breast cancer mortality has continued to increase in Brazil ( Diniz et al., 2017 ), in contrast to North American and European countries where mortality has been decreasing ( Siegel et al., 2017 ; Torre et al., 2017 ). Between 2008 and 2013, the total number of breast cancer deaths in Brazil increased by an average of 3.75% per year ( Diniz et al., 2017 ).…”
mentioning
confidence: 99%
“…Breast cancer mortality has continued to increase in Brazil ( Diniz et al., 2017 ), in contrast to North American and European countries where mortality has been decreasing ( Siegel et al., 2017 ; Torre et al., 2017 ). Between 2008 and 2013, the total number of breast cancer deaths in Brazil increased by an average of 3.75% per year ( Diniz et al., 2017 ). Thus, it is important to identify factors that are associated with poor participation in mammography screening so that service providers can target health promotion messages and screening programs more effectively.…”
mentioning
confidence: 99%
“…Ainda, entre 1985Ainda, entre -1999 proporcional (PRADO, 2002;MÜLLER, 2009; NEVES e NAFFAH, 2014). gravidez após os 30 anos; ausência ou curto período de aleitamento materno; uso de contraceptivos orais; uso de terapias de reposição hormonal; exposição a radiações ionizantes (mamografia e radioterapia); dieta rica em alimentos processados e ultraprocessados e carnes vermelhas; trabalho por turnos; e uso de sistema privado de saúde (HULKA e STARK, 1995;VINEIS e WILD, 2014;SIU, 2016;SÃO PAULO, 2017;BRASIL, 2017;DINIZ et al, 2017;FIOLET et al, 2018…”
Section: Comparação Com As Condições Socioeconômicasunclassified
“…. O estudo ecológico de DINIZ et al (2017), no Brasil, também encontrou associação a nível municipal da mortalidade com o rastreamento mamográfico e o uso de serviços privados de saúde.…”
Section: Taxas De Mortalidade Por Câncer De Mama E Câncer Do Colo Do unclassified